Project Management - Bruce, Andy.; Langdon, Ken. (London : Dorling Kindersley, 2000)
This innovative series covers a wide range of management topics. Each title is a comprehensive, compact source of easy reference for all those in - or aspiring to - a position of responsibility.
Includes index.
Keywords: Industrial project management; Business and Management